2017
DOI: 10.1016/j.celrep.2017.01.060
|View full text |Cite
|
Sign up to set email alerts
|

The Input-Output Relationship of the Cholinergic Basal Forebrain

Abstract: Summary Basal forebrain cholinergic neurons influence cortical state, plasticity, learning and attention. They collectively innervate the entire cerebral cortex, differentially controlling acetylcholine efflux across different cortical areas and timescales. Such control might be achieved by differential inputs driving separable cholinergic outputs, although no input-output relationship on a brain-wide level has ever been demonstrated. Here we identify input neurons to cholinergic cells projecting to specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
203
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(212 citation statements)
references
References 91 publications
9
203
0
Order By: Relevance
“…The final three animals were implanted at 16 mm anterior interaural with the same lateral and depth coordinates. The final lateral and anterior coordinates, and depth, were chosen to correspond to the center of the anterior portion of the Nucleus Basalis of Meynert, which would contain the highest density of projections to the prefrontal cortex [10,55,56]. At the targeted brain position, the stimulation region, which is estimated to be a 4 mm diameter sphere[29], should include the Nucleus Basalis of Meynert as well as portions of the anterior amygdala including the central nucleus, the anterior commissure, and the inferior internal globus pallidus[57].…”
Section: Star Methodsmentioning
confidence: 99%
“…The final three animals were implanted at 16 mm anterior interaural with the same lateral and depth coordinates. The final lateral and anterior coordinates, and depth, were chosen to correspond to the center of the anterior portion of the Nucleus Basalis of Meynert, which would contain the highest density of projections to the prefrontal cortex [10,55,56]. At the targeted brain position, the stimulation region, which is estimated to be a 4 mm diameter sphere[29], should include the Nucleus Basalis of Meynert as well as portions of the anterior amygdala including the central nucleus, the anterior commissure, and the inferior internal globus pallidus[57].…”
Section: Star Methodsmentioning
confidence: 99%
“…More speculatively, it is possible that cholinergic excitation of prefrontal CPn neurons also acts to couple bottom-up and top-down attentional mechanisms in two ways. First, axon collaterals of layer 5 pyramidal neurons targeting the basal forebrain may promote ACh release in other cortical areas (Gielow & Zaborszky, 2017), as activation of the PFC, including via mAChR stimulation, is sufficient to induce ACh release in the parietal cortex (Nelson et al 2005) and is necessary for sensory-evoked ACh release in primary sensory areas (Rasmusson et al 2007). Second, intracortical CPn axon collaterals contribute to top-down feedback projections within cortical hierarchies (Ueta et al 2013;Ueta et al 2014) to provide prospective information to lower order cortical areas (Larkum, 2013).…”
Section: Functional Implications Of Selective Cholinergic Excitationmentioning
confidence: 99%
“…Inhibition in the OB has been proposed as a mechanism to sharpen the odor tuning of MTC (Yokoi et al, 1995) however, the observed homogenous suppression during light stimulation is not consistent with an AON mediated sharpening of odor responses. We cannot exclude that optical stimulation is stronger and spatiotemporally more homogenous compared to "intrinsic" AON activity as a result of its input from OB (Lei et al, 2006;Kay et al, 2011), anterior piriform cortex (Haberly and Price, 1978;Luskin and Price, 1983;Haberly, 2001;Hagiwara et al, 2012), amygdala (De Carlos et al, 1989Gomez and Newman, 1992;Canteras et al, 1995;Petrovich et al, 1996), basal forebrain (Broadwell and Jacobowitz, 1976;Luiten et al, 1987;De Carlos et al, 1989;Carnes et al, 1990;Gaykema et al, 1990;Zaborszky et al, 2012;Gielow and Zaborszky, 2017) hippocampus, (Swanson and Cowan, 1977;van Groen and Wyss, 1990;Aqrabawi and Kim, 2018b) and medial prefrontal cortex (Sesack et al, 1989). While speculating about "intrinsic" modes of AON activation is complicated by these extensive connection with olfactory as well as non-olfactory centers and therefore out of the scope of this study, we could show that photostimulation did not affect general performance, as ChR2 mice were able to perform non olfactory tasks during laser stimulation (data not shown).…”
Section: Functional Role Of Modulating Aon Activitymentioning
confidence: 99%